Revised AHA and ACC Guidelines for VHD - Parry, Nicola (MD Conference Express, 2014)
This article discusses the recently released updated guidelines of the American Heart Association (AHA) and American College of Cardiology (ACC) for the management of valvular heart disease (VHD) in adults [Nishimura RA et al. Circulation. 2014; J Am Coll Cardiol. 2014], emphasizing several new items.